Studi Probabilitas Pemilihan Moda Transportasi Kereta Api Eksekutif Gajayana dan Kereta Api Eksekutif Jayabaya dengan Rute Jakarta-Malang - Putra, Dewangga Andya Mahendra; Utomo, Nugroho; Estikhamah, Fithri (Jurnal Talenta Sipil, 2024)
The train is a means of land transportation that continues to experience improvements in its services. Services and regulations change with the times, thus making PT. The Railways are making efforts to improve quality in terms of service, comfort and safety where all trains use AC facilities and eliminate all hawkers who sell on trains and at train stations in order to provide comfort to passengers. From these changes, each mode of transportation, especially the Gajayana Executive Train and the Jayabaya Executive Train, has different characteristics in terms of travel time and travel fare. Therefore, the aim of this research is to determine the probability of train selection based on the factors reviewed by distributing questionnaires and using the Stated Preference method to obtain primary data. The data obtained was then analyzed using Binomial Logit regression with Microsoft Excel software. From this research, significant results were obtained regarding the probability value of choosing a mode of transportation based on the difference in ticket prices of IDR. 40,000,- then the PKAG probability value is 0.226 and the PKAJ probability value is 0.774. So it can be concluded that respondents have more interest in the Jayabaya Executive Train because ticket prices are cheaper than the Gajayana Executive Train. Meanwhile, the probability value for choosing a mode of transportation is based on the travel time difference of -62 minutes, so the PKAG probability value is 0.904 and the PKAJ probability value is 0.096. So it can be concluded that respondents have more interest in the Gajayana Executive Train because the travel time is faster.